2010
DOI: 10.1007/s00125-010-1729-5
|View full text |Cite
|
Sign up to set email alerts
|

Metformin suppresses hepatic gluconeogenesis and lowers fasting blood glucose levels through reactive nitrogen species in mice

Abstract: Aims/hypothesis Metformin, the major target of which is liver, is commonly used to treat type 2 diabetes. Although metformin activates AMP-activated protein kinase (AMPK) in hepatocytes, the mechanism of activation is still not well known. To investigate AMPK activation by metformin in liver, we examined the role of reactive nitrogen species (RNS) in suppression of hepatic gluconeogenesis. Methods To determine RNS, we performed fluorescence examination and immunocytochemical staining in mouse hepatocytes. Sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 38 publications
0
22
1
Order By: Relevance
“…Although arctigenin activated AMPK in skeletal muscle and liver, it showed no effect on the activation of recombinant AMPK kinase, suggesting that arctigenin activated AMPK indirectly. LKB1 and CaMKK are two upstream kinases of AMPK [34], and a recent study showed that ONOO − played a critical role in AMPK activation by metformin in liver and that endothelial NOS was required for metformin action in vitro and in vivo [35]. However, our results showed that arctigenin activated AMPK independently of LKB1, CaMKK, and the ONOO − or NOS pathways.…”
Section: Discussioncontrasting
confidence: 68%
“…Although arctigenin activated AMPK in skeletal muscle and liver, it showed no effect on the activation of recombinant AMPK kinase, suggesting that arctigenin activated AMPK indirectly. LKB1 and CaMKK are two upstream kinases of AMPK [34], and a recent study showed that ONOO − played a critical role in AMPK activation by metformin in liver and that endothelial NOS was required for metformin action in vitro and in vivo [35]. However, our results showed that arctigenin activated AMPK independently of LKB1, CaMKK, and the ONOO − or NOS pathways.…”
Section: Discussioncontrasting
confidence: 68%
“…Metformin and epigallocatechin-3-gallate suppress hepatic gluconeogenesis by ROS-mediated AMPK activation in the liver (50). By using genetic models, many groups have demonstrated the acute requirement of ROS for AMPK activation, which has many beneficial metabolic effects (47,51,52). Based on the significant inhibition of AMPK and glucose uptake by NAC, we suggest that ROS generation by emodin plays an important role in the activation AMPK.…”
Section: Discussionmentioning
confidence: 88%
“…Although these initial conclusions were later refuted by the authors [16], the absence of clear data linking the mitochondrial effect of metformin to activation of hepatic AMPK still nurtures confusion. Thus, an alternative AMP-independent hypothesis involving mitochondrial-derived peroxynitrite was recently proposed, prolonging the controversy [17]. Taken together, a clarification of the mechanism by which metformin activates hepatic AMPK is required, especially in humans.…”
Section: Introductionmentioning
confidence: 99%